The dynamics of monthly changes in US swap yields: A Keynesian perspective - Tanweer Akram; Khawaja Mamun (Levy Economics Institute of Bard College, 2022)
John Maynard Keynes (1930) asserted that the central bank sways the long-term interest rate through the influence of its policy rate on the short-term interest rate. Recent empirical research shows that Keynes's conjecture holds for long-term Treasury yields in the United States. This paper investigates whether Keynes's conjecture also holds for the monthly changes in US longterm swap yields by econometrically modeling its dynamics using an autoregressive distributed lag (ARDL) approach. The econometric modeling reveals that there is statistically significant effect on the monthly changes in the Treasury bill rate on the monthly changes in swap yields of different maturity tenors after controlling for a host of macroeconomic and financial control variables. The findings from the econometric models that are estimated render a perspicacious Keynesian perspective on key policy questions and contemporary debates in macroeconomics and finance.
Keywords: E43; E50; E58; E60; G10; G12; 330; Interest Rate Swaps; Swap Yields; Short-Term Interest Rate; Monetary Policy; Federal Reserve; John Maynard Keynes